Періодичні видання НАН України з фізико-технічних і математичних наук: рівень монополізованості - Радченко, А.І.; Коваль, Н.В. (Вісник НАН України, 2020)
Статтю присвячено вивченню рівня монополізованості наукових журналів Секції фізико-технічних і математичних наук НАН України. Це третя і завершальна публікація з дослідження широти авторської аудиторії наукової періодики НАН України за період 2015–2017 рр. Як і у попередніх статтях, оцінювання авторської аудиторії журналу та рівня його монополізованості проведено на основі обчислення індексу Херфіндаля–Хіршмана, визначено кількісний зважений розподіл авторів кожного видання за афіліацією (офіційним місцем роботи). З’ясовано, що журнали з фізико-технічних і математичних наук мають здебільшого високий рівень монополізованості (54 %), 17 % з них мають середній рівень і 25 % видань — низький рівень монополізованості. This article is the third one in the cycle of publications on the monopolization level of scientific periodicals of National Academy of Sciences of Ukraine. It is devoted to the journals of Section of Physical, Engineering and Mathematical Sciences. The paper finishes the first stage of research aimed on a revealing of the author’s community of the NAS of Ukraine journals during 2015–2017. As well as in the previous articles of this cycle, the estimation of the authors community and its monopolization level was made by the Herfindahl-Hirschman index calculation. Thus, the quantitative weighted distribution of affiliation was made for each journal. The analysis of the journals of Section of Social Sciences and Humanities and the Section of Chemical and Biological Sciences was made in the articles previously published in the “Herald of the National Academy of Sciences of Ukraine” (2018, No. 9 and 2019, No. 10). It was shown that the chemical and biological journals of NAS of Ukraine have the lowest monopolization level — there are only 23 % of middlemonopolized and 27 % of low-monopolized ones. Meanwhile, only 19 % of journals of the Section of Social Sciences and Humanities have the moderate monopolization level and the rest have the high one. Journals of the Section of Physical, Engineering and Mathematical Sciences are more like chemical and biological ones. They mostly have high monopolization level (54 %), however 17 % are moderately monopolized and 25 % are low-monopolized ones.